2023
DOI: 10.1108/rpj-11-2022-0404
|View full text |Cite
|
Sign up to set email alerts
|

Bead geometry–induced stress concentration factors in material extrusion polymer additive manufacturing

Abstract: Purpose Material extrusion additive manufacturing processes inevitably produce bead-shaped surface patterns on the walls of parts, which create stress concentrations under load. This study aims to investigate the influence of such stress concentrations on the strength along the build direction (“Z-strength”). Design/methodology/approach This work consists of two main parts – an experimental demonstration to show the significance of stress concentrations on the Z-strength, followed by numerical modeling to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Despite FFF's popularity, parts fabricated with FFF tend to be weaker and more brittle than those fabricated with traditional thermoplastic formative manufacturing (e.g., injection molding, extrusion) or other forms of thermoplastic AM (e.g., powder bed fusion/selective laser sintering) 1–3 . Worse properties may be caused by poor interlayer welding, 4,5 the presence of voids, 6,7 extrudate shape, 8,9 compositional variation across the extruded road, 10 or a combination of factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite FFF's popularity, parts fabricated with FFF tend to be weaker and more brittle than those fabricated with traditional thermoplastic formative manufacturing (e.g., injection molding, extrusion) or other forms of thermoplastic AM (e.g., powder bed fusion/selective laser sintering) 1–3 . Worse properties may be caused by poor interlayer welding, 4,5 the presence of voids, 6,7 extrudate shape, 8,9 compositional variation across the extruded road, 10 or a combination of factors.…”
Section: Introductionmentioning
confidence: 99%
“…Allum et al reported that the surface topography of FFF parts, with the characteristic stacked layers of extrudate, leads to stress concentration in the notches that reduces the strength and fracture toughness even when conditions are appropriate for full welding 8 . Kundurthi et al also showed that the stress concentration factor, which is due to the geometry of stacked layers, reduces the effective z‐strength 9 …”
Section: Introductionmentioning
confidence: 99%